Felix Siauw’s Rhetoric in Responding to Public Aspirations Regarding the Phenomenon of Demonstrations and Looting on YouTube - Intan Safitri; Muktarruddin Muktarruddin (Suluah Pasaman, 2026)
This study aims to analyze Ustadz Felix Siauw's rhetoric on YouTube in response to the demonstrations and looting in August 2025. This research is important because the rhetoric of religious figures on social media plays a role in shaping public opinion on socio-political issues. This study uses a descriptive qualitative approach with an analysis of Aristotelian rhetoric, which includes ethos, pathos, and logos. Data were obtained through documentation and observation of two YouTube videos featuring Felix Siauw discussing the issues of demonstrations and looting. The results show that the element of logos is prominent through the delivery of rational arguments, cause-and-effect relationships, and an emphasis on moral principles. The elements of ethos and pathos remain present as supporting elements in building credibility and emotional engagement with the audience. These findings indicate that Felix Siauw's rhetorical strategies not only influence the audience's rational understanding of social phenomena but also build trust and emotional engagement with the message. This research contributes to the development of digital communication studies, particularly regarding the application of Aristotle's rhetoric in analyzing the communication strategies of religious figures on social media in responding to social issues